Concomitant medullary thyroid carcinoma with paraganglioma-like pattern and papillary thyroid carcinoma. (28th November 2019) - Greco, C; Brigante, G; Taliani, E; Corrado, S; Simoni, M; Madeo, B
Abstract : Summary: A 74-year-old man was referred to the Endocrinology Unit because of multinodular goiter. The dominant nodule (1.7 × 1.9 × 2.4 cm), at the medium-superior third of the left lobe, was inhomogeneously hypoechoic, with irregular margins, macrocalcifications and intranodular vascularization. Fine-needle aspiration biopsy (FNAB) was performed. The cytological diagnosis was TIR 2, benign, according to the 2013 Italian thyroid cytology classification system. Moderately high serum calcitonin (s-Ct) (61.5 pg/mL, n.r. 0–7.5) and normal CEA were detected. The Ct level in FNAB wash-out fluid (Ct-FNAB) was 1450 pg/mL. Based on s-Ct and Ct-FNAB levels, patient underwent total thyroidectomy. Macroscopically, a dominant circumscribed nodule of 2 ecm was described; the histological and immunohistochemical features identified medullary thyroid carcinoma (MTC) with paraganglioma (PG)-like pattern positive for Ct, CEA and chromogranin and negative for S-100 sustentacular cells (SC). Moreover, papillary carcinoma of 3 mm in the right lobe was also associated. No areas of hyperaccumulation of the tracer were documented at Ga68 PET/CT. No RET -proto-oncogene mutations were found. Post-surgery s-Ct levels were within normal range (4 pg/mL). Two years after thyroidectomy, the patient is still disease-free. We reported a case of sporadic and rare variant of MTC: this is the ninth described case of PG-like MTC. In this case, cytologically benign, the clinical suspicion arose from high Ct values at FNAB wash-out fluid. Even if clinical behavior of this variant seems indolent, additional studies are necessary to understand prognoses and predictive factors. Learning points: Several unusual histological variants of medullary thyroid carcinoma (MTC) have been described such as spindle cell, giant cell, clear cell, melanotic, squamous, angiosarcoma-like variants; even rarer is the paraganglioma (PG)-like pattern. We here describe a case of medullary PG-like thyroid carcinoma in a 74-year-old man. This is a rare histological variant of MTC hardly diagnosed by cytology, since immunohistochemical investigations are necessary. Measurement of calcitonin both in serum and in wash-out fluid from fine-needle aspiration could be an additional tool for an early and non-invasive identification of these variants.